COMPARACIÓN DEL RENDIMIENTO PRODUCTIVO DE GALLINAS PONEDORAS COMERCIALES HY LINE BROWN EN LAS ESTACIONES DE VERANO E INVIERNO EN LA AVÍCOLA J.B. S.A.C. - Avila Pérez, Diana del Pilar (2014)
In the present research work was carried out in the company JB Poultry S.A.C. located in the district of Huanchaco, Liberty department in order to determine the effect of season (summer and winter) on performance of laying hens Hy Line Brown Line. 10002 hens were used at two different ages distributed under a design of randomized complete block where the seasons as treatments and the age of the hens was considered as blocks. The egg laying rate was significantly higher in the winter than in the summer in both comparison groups (p <0.01). The levels of differences between averages ranged from 2.6% for group I and 8.6% for group II. The amount of kilos produced by hens during the winter time was higher than the amount produced in the summer (p <0.01). The calculated differences between the means of both groups ranged from 131.6 kg for group I and 643.3 kg for the II. Weekly food consumption by treatment in the comparison group I was statistically similar between the means of the two stations (p> 0.05). Statistically significant differences in the winter season (113.9 kg) compared to the summer season (109.2 kg) (p <0.01) in group II was determined. In group I no statistically significant differences in feed conversion between the means of the two stations was calculated: 11.2 vs 11.1 (p> 0.05). In group II statistically significant differences, the winter season (1.93) compared to summer (2.03) (p <0.01) were determined. With respect to mortality differences statistically significantly (p <0.01) being higher in the summer season with 7% while in winter mortality of 4.5% was recorded were recorded. It is concluded that the production parameters of the laying hen in the two comparison groups were better in the winter than in the summer season